165k views
19 votes
Simplify:
(3x+4) (2x - 5)

Simplify: (3x+4) (2x - 5)-example-1

2 Answers

4 votes

Answer:

C

Explanation:

Given

(3x + 4)(2x - 5)

Each term in the second factor is multiplied by each term in the first factor, that is

3x(2x - 5) + 4(2x - 5) ← distribute both parenthesis

= 6x² - 15x + 8x - 20 ← collect like terms

= 6x² - 7x - 20 → C

User Quiver
by
4.5k points
10 votes

Answer:

6x^2-7x-20 (c)

Explanation:

(3x+4)(2x−5)

=(3x+4)(2x+−5)

=(3x)(2x)+(3x)(−5)+(4)(2x)+(4)(−5)

=6x^2−15x+8x−20

=6x^2-7x-20

User Kiliandeca
by
4.2k points